The quickie : a novel - Patterson, James, 1947- (Little, Brown, 2007)
When Lauren discovers her husband is with another woman, she decides to take revenge by beating him at his own game--but her night of passion takes a dangerous turn when she witnesses an unbelievable crime. Her shocking secret threatens to tear her life apart, pitting her need to uncover the truth against her fear that the truth may be too horrible to bear. And whichever choice she makes could cost her job, her marriage, even her life.--From publisher description.